The Necessity Of Learning Educational Management, Administration And Planning To Overcome The Challenges Faced By The Indian / Bharatiya Education - Dr. Prachi Anarth (Educational Administration: Theory and Practice, 2024)
Preparation, advance planning and management are very important before doing any work. Educational management is a part of holistic education. In today's era, education management is absolutely necessary to do the job of teaching properly. Educational management refers to the administration of education in which a group mobilizes human and material resources. The purpose of education management is to implement the strategy of education system, structure supervision, planning etc. in a smooth manner. Education is the acquisition of values, beliefs, good habits and positive attitudes through knowledge, understanding, application and skills. Institutions in the education system are government ministries, statutory boards and bodies, schools, colleges and universities etc. Management of education system is mainly implemented through the combined efforts of students, principals, teachers, non-teaching staff, administrative staff, parents. , government representatives etc. Management is required at all levels of the educational ecosystem. Management includes planning, organizing, implementing, reviewing, evaluating and integrating the organization. The history of educational management is very old. Notable ancient and present educational institutions in India are Maharishi Bharadwaj Ashram, Maharshi Kanva Munir Ashram, Vasishthar Ashram, Raja Janaka Pratishthan, Vedavyas, Maharshi Sandipani, Mata Sabari, Swami Dayananda, Taxila, Nalanda, Ramakrishna Math and Mission Vichikananda established by him. Rishi Aurobindo Ashram founded by Rabindranath Tagore established Visva Bharati and Sriniketan etc. in Bolpur. Educational management like other branches of management is a textual subject. Gurukul system of education was prevalent in ancient times. Guru and disciple lived together in the ashram. Guru-shishe parampara i.e., Guru-shishe tradition, study, education, reformation and culture flowed among students since time immemorial. Educational management, administration and planning are now separate courses due to the complexity of the social system. This course was first popularized in the United States during World War II. In the 1960s, the U.K. also introduced this course. It was launched very promisingly in India, very late. The course is currently taught in some private universities in various states including Delhi, Punjab. This course also teaches research programs at the National University of Education Planning and Administration (NUEPA).